Perspectives on data analytics for gaining a competitive advantage in football: Harnessing data for decision support - Hecksteden, A.; Kempe, M.; Berger, J. (Science and Medicine in Football, 2025)
In this issue, Olthof and Davis highlight the potential of computational methods for gaining a competitive advantage in football and call for a closer collaboration between football and data science experts to fully leverage these opportunities. While we agree in principle with both aspects, we would like to amend some considerations that may contribute nuances to this perspective.